2021
DOI: 10.1186/s12960-021-00652-6
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal mentorship intervention to improve surgical quality in Tanzania’s Lake Zone: a convergent, mixed methods assessment

Abstract: Background Safe, high-quality surgical care in many African countries is a critical need. Challenges include availability of surgical providers, improving quality of care, and building workforce capacity. Despite growing evidence that mentoring is effective in African healthcare settings, less is known about its role in surgery. We examined a multimodal approach to mentorship as part of a safe surgery intervention (Safe Surgery 2020) to improve surgical quality. Our goal was to distill lessons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…This findings provides evidence that the training and onsite mentorship intervention to have a statistically significant positive impact on the RMNH service performance among healthcare workers. The finding of the current study is consistent with another study from the same context that used a multimodal mentorship intervention for improving the quality surgical care [ 44 ]. Moreover, other studies reported that a mentorship intervention that follows training, uses a side-by-side approach, high-quality mentee–mentor relationships, and provides nonjudgmental feedback leads to success in low-resource settings [ 28 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This findings provides evidence that the training and onsite mentorship intervention to have a statistically significant positive impact on the RMNH service performance among healthcare workers. The finding of the current study is consistent with another study from the same context that used a multimodal mentorship intervention for improving the quality surgical care [ 44 ]. Moreover, other studies reported that a mentorship intervention that follows training, uses a side-by-side approach, high-quality mentee–mentor relationships, and provides nonjudgmental feedback leads to success in low-resource settings [ 28 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of the current study is consistent with another study from the same context that used a multimodal mentorship intervention for improving the quality surgical care [ 44 ]. Moreover, other studies reported that a mentorship intervention that follows training, uses a side-by-side approach, high-quality mentee–mentor relationships, and provides nonjudgmental feedback leads to success in low-resource settings [ 28 , 44 , 45 ]. Therefore, it is plausible that the training that supplemented with mentorship might be the effective approach for skills improvement among healthcare workers.…”
Section: Discussionsupporting
confidence: 91%
“…In LMICs, research on the role of mentorship in surgery is at a nascent stage [ 53 , 54 ] and surgical mentorship program implementation has not been sufficiently analyzed to guide policy and practice; this is important to successfully design and implement mentorship programs [ 6 ]. We found results from implementing SS2020 mentorship in Ethiopia similar to Tanzania [ 5 ], with strong support from mentees and similar perceived impacts, including safer care, strengthened surgical ecosystems, increased confidence, and stronger learning cultures in both countries. Common supportive features included a holistic approach, multidisciplinary mentorship team, psychologically safe relationships, mentors that were friendly, accessible, and understanding of the local context, and a receptive implementation climate.…”
Section: Discussionmentioning
confidence: 92%
“…In 2015, the Lancet Commission on Global Surgery placed surgical workforce development on top of the health, welfare, and economic development agenda [3]. Building the capacity of surgical systems through mentorship is a promising strategy to improve access and quality of care [4,5]. However, implementation of surgical mentorship in African healthcare settings has not been thoroughly analyzed [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the years after the life of the World Alliance for Patient Safety (2015)(2016)(2017)(2018)(2019)(2020)(2021), the WHO has moved further to engage with a bigger number of stakeholders DOI: 10.4236/aid.2022.123036 468 Advances in Infectious Diseases and partners in order to be able to improve patient safety globally [4]. One of the early efforts was the launch of the Third Global Patient Safety Challenge, called "Medication Without Harm," which aimed at addressing medication safety [13] [14].…”
Section: Introductionmentioning
confidence: 99%